Hubungan Pendapatan, Tingkat Asupan Energi dan Karbohidrat dengan Status Gizi Balita Usia 2-5 Tahun di Daerah Kantong Kemiskinan - Lutfiyatul Afifah (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2019)
Background: Nutritional status of toddlers is considered important since they are generally more susceptible to nutritional problem. Some factors that affect them is level of nutrient intake, which include level of energy intake, carbohydrate intake, and family income. Family income is associated with the ability to provide food, thus affecting the level of nutrient intake for the family.Objectives: The objective of the study was to analyze the correlation between incomes, level of energy and carbohydrate intake with nutritional status of toddlers aged 2-5 years in Lenteng sub-District, Sumenep.Methods: the design of this study was cross sectional. Sample size was 70 parents of toddlers aged 2-5 years in Lenteng sub-District, Sumenep. Weight and height of the toddlers were measured to determine the nutritional status of the toddlers. Interviews with parents were also conducted to determine the characteristic of the toddlers and the family income. Lastly, 2 x 24 hours food recall was used to examine the level of their nutrient intake. The data were analyzed by using Spearman correlation test with α= 0.05.Results: The results showed that 57.1% toddlers were in low income category. 65.7% toddlers were in inadequate level of energy intake. 95.7% were in inadequate level of carbohydrate intake. Prevalence of toddlers with normal nutritional status normal were 84.3%, 11.4% was malnourished, while 2.9% was severely malnourished. The result showed that level of energy intake and carbohydrate intake are related to nutritional status of toddlers (p=0.040) and (p=0.045). However, there was no correlation found between family incomes with toddlers' family income.Conclusions: Family income was not found to be related to the nutritional status of toddlers. While the lower level of nutrient intake can potentially affect nutritional problem among toddlers. Thus, an adequate nutrient intake is required to help toddlers meet their balanced nutritional needs.ABSTRAK Latar Belakang: Status gizi balita penting diperhatikan karena balita rentan mengalami masalah gizi. Masalah gizi pada balita masih banyak terjadi. Status gizi balita dapat dipengaruhi oleh beberapa faktor diantaranya yaitu tingkat asupan zat gizi termasuk energi dan karbohidrat serta pendapatan keluarga. Rendahnya asupan zat gizi dapat mengakibatkan masalah gizi balita. Pendapatan keluarga berkaitan dengan kemampuan memenuhi asupan pangan keluarga.Tujuan: Untuk menganalisis hubungan antara pendapatan, tingkat asupan energi, dan karbohidrat dengan status gizi balita usia 2-5 tahun di Kecamatan Lenteng Kabupaten Sumenep.Metode: Desain penelitian yang digunakan adalah cross sectional. Jumlah sampel 70 orang tua balita berusia 2 hingga 5 tahun. Pengukuran berat badan dan tinggi badan balita untuk menilai status gizi. Wawancara kepada orang tua untuk mengetahui karakteristik balita dan pendapatan keluarga serta food recall 2 x 24 hours untuk mengetahui tingkat asupan balita. Data dianalisis menggunakan uji korelasi spearman dengan α= 0,05.Hasil: Sebanyak 57,1% responden berpendapatan rendah. Sebanyak 65,7% tingkat asupan energi adalah inadequate dan 95,7% karbohidrat adalah kurang. Prevalensi status gizi normal 84,3%, kurus 11,4% dan sangat kurus 2,9%. Hasil analisis menyebutkan ada hubungan antara tingkat asupan energi (p=0,040) dan tingkat asupan karbohidrat (p=0,045) dengan status gizi balita. Sedangkan pendapatan tidak berhubungan dengan status gizi balita (p=0,649).Kesimpulan: Pendapatan keluarga berhubungan dengan status gizi balita. Tingkat asupan zat gizi yang kurang dapat meningkatkan risiko masalah gizi balita. Maka perlu dilakukan peningkatan asupan zat gizi untuk memperoleh status gizi yang baik atau normal.